2012
DOI: 10.1371/journal.pone.0045887
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cytochrome P450 in Pentachlorophenol Transformation in a White Rot Fungus Phanerochaete chrysosporium

Abstract: The occurrence of cytochrome P450 and P450-mediated pentachlorophenol oxidation in a white rot fungus Phanerochaete chrysosporium was demonstrated in this study. The carbon monoxide difference spectra indicated induction of P450 (103±13 pmol P450 per mg protein in the microsomal fraction) by pentachlorophenol. The pentachlorophenol oxidation by the microsomal P450 was NADPH-dependent at a rate of 19.0±1.2 pmol min−1 (mg protein)−1, which led to formation of tetrachlorohydroquinone and was significantly inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 50 publications
1
10
0
1
Order By: Relevance
“…In P. chrysosporium , six PAH-responsive CYP genes identified by genome-wide microarray screening were induced and upregulated upon varying ring-sized PAHs, and their catalytic function towards various PAHs was determined using recombinant enzymes [ 51 ]. Furthermore, the induction of CYPs by pentachlorophenol (PCP) was also observed in P. chrysosporium , in which only the PCP-induced fungal microsomes led to the oxidation of PCP to form tetrachlorohydroquinone [ 68 ]. Remarkably, the transcriptional regulation of CYP-dependent metabolic pathways can be alternatively induced or upregulated by defined high or low nitrogen conditions, as observed in P. chrysosporium, C. versicolor, P. placenta , and A. oryzae [ 40 , 69 , 70 ].…”
Section: Systematic Approach To Heterologous Expression Of Fungal Cypmentioning
confidence: 99%
“…In P. chrysosporium , six PAH-responsive CYP genes identified by genome-wide microarray screening were induced and upregulated upon varying ring-sized PAHs, and their catalytic function towards various PAHs was determined using recombinant enzymes [ 51 ]. Furthermore, the induction of CYPs by pentachlorophenol (PCP) was also observed in P. chrysosporium , in which only the PCP-induced fungal microsomes led to the oxidation of PCP to form tetrachlorohydroquinone [ 68 ]. Remarkably, the transcriptional regulation of CYP-dependent metabolic pathways can be alternatively induced or upregulated by defined high or low nitrogen conditions, as observed in P. chrysosporium, C. versicolor, P. placenta , and A. oryzae [ 40 , 69 , 70 ].…”
Section: Systematic Approach To Heterologous Expression Of Fungal Cypmentioning
confidence: 99%
“…Extracellular Peroxidases and laccase have been reported to be the key enzymes involved in the degradation of recalcitrant aromatic polymers by WRF (Mester and Tien 2000; Zahmatkesh et al 2010; Mendonça Maciel et al 2010). Cytochrome P450 (CYP) enzymes comprise another group of enzymes of which their involvement in the degradation of some organic compounds by WRF has been demonstrated (Ning and Wang 2012; Kelly and Kelly 2013; Zhang et al 2015). CYPs are membrane-bound hemoproteins that catalyze hydroxylation, epoxidation and monooxygenation reactions (Neve and Ingelman-Sundberg 2008; Aranda 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These genes play a role in the adaptation of fungi to lignin decomposition [38]. P450 mediated pentachlorophenol oxidation [39], the CYP512, CYP5136 and CYP5150 families can oxidize a wide range of hydrocarbons, including phytochemicals and key metabolic intermediates in fungi, such as steroids, indicating that they play a role in the primary and secondary metabolism of fungi [40]. Matsuzaki et al studied the intracellular changes of P. chrysosporium during benzoic acid metabolism at the proteome and metabolic level, and found that aryl alcohol dehydrogenase, aromatic aldehyde dehydrogenase and cytochrome P450 play a key role in benzoic acid metabolism [31].…”
Section: Differential Gene Expression As a Function Of Wood Stimulusmentioning
confidence: 99%